(untitled) (Actual Problems of Psychology in Educational Institutions, 2023)
The article is devoted to the problem of moral development of modern teenagers by means of school education. The essential dimensions of the moral development of the individual are analyzed, the development of the moral consciousness of modern teenagers as an effect of the socialization of the individual is outlined. The results of measuring the value orientations of teenagers using the method of M. Rokych are presented. Special attention is paid to the development potential of foreign literature. The author examines in detail the educational and developmental resource of Harper Lee’s novel “To Kill a Mockingbird” in the formation of the moral consciousness of the personality of older teenagers. The possibilities of this novel in the development of tolerance and sense of justice among teenagers have been revealed.